GSC-based spatial voice activity detection for enhanced speech coding in the presence of competing speech. - Hoffman, M.W (IEEE Transactions on speech and audio processing)
An array of microphones is used for both noise suppression and spatial voice activity detection (SVAD). A generalized sidelobe canceler (GSC) is employed for robust adaptive interference rejection and the signals within the GSC are also exploited to provide speech activity detection for the desired signal. The SVAD shows promising results for the difficult case of an interfering speaker